Experimental studies of sowing machine-tractor unit consisting of tractor and Vega-8 W Profi seeder (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article presents the results of experimental studies of the sowing machine-tractor unit consisting of tractor and the Vega-8 W Profi seeder. It has been established that the efficiency of agricultural operations largely depends on the productivity of MTA. It has been determined that conventional agricultural methods of growing crops often lead to soil compaction and increased greenhouse gas emissions. During experimental research, a measuring system for the dynamics and energy of mobile machines was used. The measuring system is designed to determine the kinematic, dynamic, power and energy characteristics of mobile machines and their elements during road, field and bench tests. During the first series of studies, the influence of the design parameters of the unit on the dynamics and oscillations of the elements was determined, as well as in order to assess the technical and economic indicators. At a speed of 2.8 m/s, the acceleration of IVP-3, which is installed on the seeder saddle, has the largest range of oscillations. These indicators are influenced by the proximity of the fan of the pneumatic system of the seeder. The main oscillation energies of the elements of the unit are at frequencies of 5, 22 and 30-35 Hz. During the second series of studies, differences in the oscillations of the seeding units of the seeder were determined. The main energy of oscillations (amplitude of vibration accelerations) of the seeder seeders is at frequencies of 3, 20, 28, 30 Hz at a speed of 2.8 m/s. The amplitudes of vibration accelerations of the first and last seeding units at frequencies of 28–30 Hz are lower than the amplitudes of vibration accelerations of the fourth and fifth. The experimental studies carried out in the PSP made it possible to assess the technical and operational indicators of the sowing unit. Indicators of soil condition meet the conditions for sowing grain crops. Soil moisture in layers of 0-5 cm was 21.4%; 5-10 cm – 23.9 %, 10-15 cm – 22.9 %. Optimization of the design parameters of the unit made it possible to improve technical and operational indicators. In the modernized version of the sowing MTA, productivity was increased by 15% to 5.2 ha/h; Fuel consumption per hectare decreased by 0.2 kg/ha (18%) to 2.4 kg/ha.
Keywords: experimental research; sowing unit; tractor; seeder; measuring system; acceleration; technical and operational indicators